Distribution of Social Assistance by Election Candidate Pairs according to Ulama' Nahdlatul Ulama and Muhammadiyah - Nada, Nihalun; Sunan Umam, Zulfi; Musta'an Najikh, Ahmad (Komparatif: Jurnal Perbandingan Hukum dan Pemikiran Islam, 2025)
Abstract: Social assistance distributed by pairs of election candidates during the campaign has caused debate among politicians and clerics. With this case, the two largest community organizations in Indonesia, namely Nahdlatul Ulama and Muhammadiyah, gave a fatwa on the distribution of social assistance during the campaign period. This study explains and analyzes the problemof social assistance which is equated with money politics and compares the opinions between Ulama Nahdlatul Ulama and Ulama Muhammadiyah. The data in this study was collected using library research. The data analysis technique uses the techniqueof descriptive analysis and comparative approach to analyze the similarities and differences of the opinions of Nahdlatul Ulama and Muhammadiyah. The results of this study conclude that Nahdlatul Ulama and Muhammadiyah gave a fatwa that receiving social assistance from the pair of election candidates during the campaign period is haram. This is because social assistance is equated with money politics and risywah which is legally haram. However, both of them gave the fatwa only as a suggestion, not as a binding Islamic law. This is because both consider the economic situation of the Indonesian people.